Simple Measurement System for Biological Signal Using a Smartphone - Ryoichi Miyauchi; Koichi Tanno; Hiroki Tamura (International Journal of Electrical and Computer Engineering (IJECE), 2018)
This paper describes simple measurement system for biological signal using smartphone. The proposed system consists of an instrumentation amplifier, a filter and an AC/DC converter. The biological signal is converted to the digital data through the microphone terminal with A/D converter in the smartphone. In many cases, the circuits require the power sources such as the cell batteries, however, the proposed system is supplied the power through the earphone terminal of the smartphone. Therefore, the proposed system no require the batteries. The software of this system parallelizes the processing so that the earphone output and the microphone terminal can be executed at the same time. The proposed system was verified through the measurement of surface electromyogram using discrete parts and iOS. Results of experimentation, the proposed system was operating correctly.